A program needs-driven approach to selecting dietary assessment methods for decision-making in food fortification programs - Coates, Jennifer; Colaiezzi, Brooke; Fiedler, John L.; Wirth, James; Lividini, Keith; Rogers, Beatrice L. (SAGE Publications, 2012)
Dietary assessment data are essential for designing, monitoring, and evaluating food fortification and other food-based nutrition programs. Planners and managers must understand the validity, usefulness, and cost tradeoffs of employing alternative dietary assessment methods, but little guidance exists.To identify and apply criteria to assess the tradeoffs of using alternative dietary methods for meeting fortification programming needs.Twenty-five semistructured expert interviews were conducted and literature was reviewed for information on the validity, usefulness, and cost of using 24-hour recalls, Food Frequency Questionnaires/ Fortification Rapid Assessment Tool (FFQ/FRAT), Food Balance Sheets (FBS), and Household Consumption and Expenditures Surveys (HCES) for program stage-specific information needs. Criteria were developed and applied to construct relative rankings of the four methods.Needs assessment: HCES offers the greatest suitability at the lowest cost for estimating the risk of inadequate intakes, but relative to 24-hour recall compromises validity. Design: HCES should be used to identify vehicles and to estimate coverage and likely impact due to its low cost and moderate-to-high validity. Baseline assessment: 24-hour recall should be applied using a representative sample. Monitoring: A simple, low-cost FFQ can be used to monitor coverage. Impact evaluation: 24-hour recall should be used to assess changes in nutrient intakes. FBS have low validity relative to other methods for all programmatic purposes.Each dietary assessment method has strengths and weaknesses that vary by context and purpose. Method selection must be driven by the program's data needs, the suitability of the methods for the purpose, and a clear understanding of the tradeoffs involved.